Prediction of Combined Mesiodistal Width of Unerupted Permanent Canine and Premolars using Moyer’s Mixed Dentition Analysis in Nepalese Newar Population - Shrestha, Amrita; Pradhan, Dilesh (Orthodontic Journal of Nepal, 2019)
Introduction: Moyer’s probability table is most commonly used to predict the mesiodistal width of permanent canines and premolars in mixed dentition. However, the table was formulated using data from Caucasian population. This study was performed to compare the Moyer’s prediction table with actual value in Nepalese Newar population as ethnicity is one of the important factor to determine teeth width. Materials & Method: Combined mesiodistal width of permanent canine and premolars were measured in 150 study models of Nepalese Newar orthodontic patients (75males and 75 females). The value was compared with the Moyer’s prediction table at all probability level. Result: There was no statistically significant difference between the actual combined width and that predicted from Moyer’s table at 85% probability level for maxilla and at 75% level for mandible in male, at 95% probability level for maxilla and at 85% probability level for mandible in female. Conclusion: Moyer’s probability level can be used to predict the combined mesiodistal width of permanent canines and premolars in Nepalese Newar population but at specific probability level.